Composition for improving lipid profile with anti-atheromatous properties. - Amom, Zulkhairi; Mohd Esa, Norhaizan; Azlan, Azrina; Abd. Kadir, Khairul Kamilah (2009)

(untitled)
The present invention discloses a composition useful as a functional food, a food article or a food material, which is excellent in reducing total cholesterol level, low density lipoprotein cholesterol (LDL-c) level, ratio of low density lipoprotein cholesterol (LDL-c) to high density lipoprotein cholesterol (HDL-c) level in plaque formation and raising high density lipoprotein cholesterol (HDL-c) level in order to reduce the risk of being susceptible to hypercholesterolemia and suppressing the risk of cardiovascular disease, and also is economical and safe with respect to side effects, by containing germinated brown rice, preferably in the amount of 10% to 30% by weight of daily diet.